2018
DOI: 10.1002/ags3.12202
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted surgery for rectal cancer: Current state and future perspective

Abstract: Interest in minimally invasive surgery has increased in recent decades. Robotic‐assisted laparoscopic surgery (RALS) was introduced as the latest advance in minimally invasive surgery. RALS has the potential to provide better clinical outcomes in rectal cancer surgery, allowing for precise dissection in the narrow pelvic space. In addition, RALS represents an important advancement in surgical education with respect to use of the dual‐console robotic surgery system. Because the public health insurance systems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 68 publications
(77 reference statements)
1
36
0
5
Order By: Relevance
“…Similar results were also reported in a comparative study using open, laparoscopic, and robotic approaches for right-sided colon cancer [56]. A meta-analysis study further showed longer RALS operating time due to docking and undocking of a robotic cart which has been rectified in da Vinci Xi system [57]. These studies suggest that despite comparable oncologic outcomes by the robotic approach, large and prospective randomized controlled trials are absolutely required to draw a definite conclusion.…”
Section: Colorectal Cancersupporting
confidence: 71%
“…Similar results were also reported in a comparative study using open, laparoscopic, and robotic approaches for right-sided colon cancer [56]. A meta-analysis study further showed longer RALS operating time due to docking and undocking of a robotic cart which has been rectified in da Vinci Xi system [57]. These studies suggest that despite comparable oncologic outcomes by the robotic approach, large and prospective randomized controlled trials are absolutely required to draw a definite conclusion.…”
Section: Colorectal Cancersupporting
confidence: 71%
“…The steps are further facilitated by the magnification of the laparoscope. However, laparoscopic rectal surgery is a labor-intensive procedure with a significant learning curve that is estimated to be around 40-90 cases[ 23 ]. The critical portion of the TME as such requires a high level of expertise.…”
Section: Benchmarks Of Surgical Techniquementioning
confidence: 99%
“…The instruments are touted as having seven ranges of motion and behave more like a normal human wrist. Many studies found the learning curve to be quicker at around 15-44 cases[ 23 ]. Furthermore, the robot offers an ergonomic advantage as the surgeon sits down for most of the procedure.…”
Section: Benchmarks Of Surgical Techniquementioning
confidence: 99%
“…1 Since the first descriptions of robotic-assisted colectomy in 2001, 2 the number of robotic colorectal procedures performed worldwide has rapidly increased. 3 The introduction of new technologies in surgery is not free of risks and poses questions concerning surgeon training and how to ensure patient safety.…”
Section: Introductionmentioning
confidence: 99%